PENGARUH PERTUMBUHAN EKONOMI, PENDUDUK, DAN PENDIDIKAN TERHADAP KEMISKINAN DI KABUPATEN SIDOARJO 2014-2023 - Azizatun Fitriani; Arga Christian Sitohang (Widya Balina, 2025)
This study aims to analyze the influence of economic growth, population, and education on poverty in Sidoarjo Regency during the period 2014–2023, motivated by the persistently high poverty rate despite the region experiencing rapid economic growth and industrial development. Using secondary data from BPS and analyzed quantitatively through multiple linear regression with the assistance of SPSS, this study found that the three variables simultaneously have a significant effect on poverty, while partially, education is the most effective factor in reducing poverty compared to economic growth and population, which have a negative but not significant effect. These findings highlight the importance of equitable distribution and improvement in the quality of education as a primary strategy for poverty alleviation, as well as the need for more inclusive economic policies. Further research is recommended to include other variables such as income inequality, unemployment, and the quality of infrastructure to make the analysis of poverty determinants more comprehensive